Managing Electronic Prescribing Adoption to Improve Physician Compliance and Service Quality - Andrew Suprayogi; Purwadhi; Budi Santoso (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The transition from manual to electronic prescribing still faces significant challenges, leading to data inconsistencies, potential medical errors, and service inefficiencies. This study aims to analyze the system adoption planning, management’s efforts to facilitate doctors, and identify the main obstacles affecting compliance. This research uses a qualitative approach to find that the hospital adopted the electronic prescribing system with a pragmatic and integrated approach, choosing a free platform that is integrated with the national “Satu Sehat” program. The main obstacles found include the system’s functional limitations, such as the absence of template and autocorrect features, and difficulty in inputting compounded medication dosages, as well as user factors, namely old habits and resistance to change. A more user-friendly electronic prescribing model was developed that includes features desired by medical personnel, such as repeat order, prescription templates, autocorrect, and automatic labels. The model’s trial showed an increase in efficiency, speed, and convenience, which can significantly improve doctor compliance with system usage. This thesis supports the national health digitalization policy and offers a practical solution to improve the quality of service and patient safety.